Issues in religion and education : whose religion? - Beaman, Lori G.; Van Arragon, Leo. (International Studies in Religion and Society, 2015)
Issues in Religion and Education, Whose Religion? is a contribution to the dynamic and evolving global debates about the role of religion in public education. This volume provides a cross-section of the debates over religion, its role in public education and the theoretical and political conundrums associated with resolutions. The chapters reflect the contested nature of the role of religion in public education around the world and explore some of the issues mentioned from perspectives reflecting the diverse contexts in which the authors are situated. The differences among the chapters reflect some of the particular ways in which various jurisdictions have come to see the problem and how they have addressed religious diversity in public education in the context of their own histories and politics.